077 An unusual presentation of antibody negative autoimmune encephalitis: a case report. (29th July 2019) - Upadhyay, Viral; Malkan, Ashish; Park, Hyunmin
Abstract : Introduction: Immune-mediated encephalitis can occur in the absence of measurable pathogenic antibodies in CSF or serum. Methods and results: We present the case of a 29-year-old Sudanese woman presented with four days history of meningism. She is three months post-partum with her fifth child and does not have significant past medical history. She is a current smoker with history of methamphetamine and heroin use until 5 years ago. There were no focal neurological deficits on examination. CT brain was normal and her CSF had 420×10 6 /L leucocytes (Polymorphs 18, Mononuclears 402). Three days later, she deteriorated clinically with GCS 11 and developed left sided hemiplegia requiring intubation and ventilation in intensive care. The CSF culture along with autoimmune encephalitis panel, anti-neuronal antibodies, HSV, VZV, Enterovirus, cryptococcal antigen, TB quantiferon, HIV, Malaria were negative. Her immunology tests were unremarkable including rheumatoid factor, complements, anti-nuclear antibodies, dsDNA, PR3, MPO, RNP, Smith, Ro, La, Scleroderma 70 and Jo-1 antibodies. The MRI Brain showed persistent changes in right hemispheric cortical and subcortical gyriform FLAIR hyperintensities which were also present in DWI images. The EEG showed right temporo-occipital region 7–8 Hz rhythmic discharges with generalised diffuse slowing. She had right parietal lobe brain biopsy which shows perivascular and intramural inflammation by mononuclear cells almost comprised of CD3 T-cells consistent with encephalitis associated with secondary lymphocytic vasculitis. She was treated with intravenous pulsed methylprednisolone and IVIg followed by plasma exchange. Then given high dose oral corticosteroids with slow tapering and intravenous Cyclophosphamide four weekly. Significant neurological improvement noted over next 8 weeks with patient being alert and participating in ongoing multidisciplinary rehabilitation for hemiplegia. Conclusion: A case of cerebral biopsy confirmed, CSF and serum antibody-negative encephalitis is presented.